(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article presents a comprehensive analysis of international accounting systems in Uzbekistan. The study aims to compare Uzbekistan’s accounting practices with international standards, identifying similarities, differences, challenges, and potential areas for improvement. By examining the country’s accounting regulations, financial reporting practices, and their alignment with global standards, this research sheds light on Uzbekistan’s progress in adopting internationally accepted accounting principles.